Decentralisation in Africa: A Pathway out of Poverty and Confl ict - Gordon Crawford , Christof Hartmann (Amsterdam University Press, 2008)
Decentralisation entails the transfer of power, responsibilities and finance from central government to sub-national levels of government at provincial and/or local levels. Its current popularity, especially in the developing world, is unparalleled, with 80 per cent of all developing and transition countries undertaking some form of decentralisation over the past two decades (ICHRP 2005: 11). In Africa south of the Sahara , the focus of this book, there are few countries that have not implemented decentralisation reforms. Th is is remarkable, as Africa has a long history of formally centralised rule which dates back to colonial times, and in some instances much beyond. Independence constitutions did provide, at least in the former British colonies, for a fully established system of local government with elected councils. Th ese had responsibilities for the delivery of services such as education , health, roads, water supply and agricultural extension, as well as a level of resources. Although attempts at state centralisation in independent Africa might not have been as successful as intended, the imperative of nation-building, the realities of single-party or military rule and the necessities of centralised planning led to the marginalisation or outright suppression of these elected local and district councils and their competencies throughout the late 1960s and 1970s. In their support for modernisation and Keynesianism at that time, the donor community equally pressed for the establishment of strong central state institutions. Local government did continue to exist in many places, but with little power and resources, and thus local authorities lost both their role in the political and development process and also their legitimacy with local populations. Few authoritarian regimes were willing to cede any control over resources to other state institutions, with the notable exception of Nigeria ’s military regime which initiated a substantial decentralisation programme in 1976.